Essential Competencies of Public Health Professionals in Disaster Management: A Scoping Review - Raharjo, Agung; Januar Ariyanto; Farahul Jannah (Advances in Healthcare Research, 2025)
Purpose: This scoping review aimed to systematically identify core competencies for public health professionals in disaster management. Research Method: We analyzed 22 studies (2002-2024) from PubMed/MEDLINE, Scopus, and Web of Science using Arksey and O’Malley’s scoping review framework. Included studies addressed competencies for disaster preparedness, response, and recovery. Results and Discussion: The review identified seven critical competency domains: disaster preparedness and risk reduction, leadership and crisis management, communication and digital tool utilization, psychosocial support, community engagement with cultural competency, inter-agency coordination, and post-disaster recovery systems. Leadership and community-centered approaches were universally essential, while technological competencies, such as GIS and proficiency in social media, represented emerging needs. Significant gaps were noted in climate-related disaster frameworks and standardized global training protocols. Implications: Findings underscore the urgent need to validate competencies in field settings, integrate climate science into training programs, and develop standardized frameworks for resource-limited regions. These directly inform public health curriculum development and policy initiatives aimed at enhancing workforce preparedness for evolving disaster scenarios, including climate-related emergencies and pandemics.